A Low-Cost Improvised Nerve Stimulator is Equivalent to High-Cost Muscle Stimulator for Anorectal Malformation Surgery - Short, Scott; Kimble, Keith; Zhai, Shiwei; Frykman, Gregory; Frykman, Philip (European Journal of Pediatric Surgery, 2013)
Aim Our hypothesis is that an improvised low-cost peripheral nerve stimulator is equally effective compared with a high-cost muscle stimulator for anorectal malformation surgery.Methods A modified Micro Stim (MS) peripheral nerve stimulator was compared with the Peña Muscle Stimulator (PS2) on identification of muscle groups during surgery, tissue energy delivery, and cost. A consecutive series of 6 patients (5 boys) with weight 5.9 to 11 kg underwent posterior sagittal anorectoplasty (PSARP). The types of malformations included four prostatic fistulae, one bulbar fistula, and one vestibular fistula. In the course of each operation, both MS and PS2 devices were used to identify muscle groups in a head-to-head comparison with video documentation. The energy delivery was determined using a digital oscilloscope at settings used during the operations (#9 on the MS and 120 mA on the PS2). Price quotes for each device were obtained from commercial vendors.Results The subjective assessment of the surgical team was that both devices demonstrated equivalent utility in identifying critical muscle groups, although the MS probe was less convenient to use. There were no intraoperative complications, including tissue burns with either device, and no postoperative complications. The energy delivery of the devices was similar, 23.5 mW and 25.3 mW for the MS and PS2, respectively. The cost of the MS was US$ 162 and the PS2 was US$ 12,371.Conclusion The MS nerve stimulator demonstrated equivalent effectiveness compared with the PS2 muscle stimulator at 75-fold lower cost. The MS device may serve as a low-cost effective tool for PSARP.
Keywords: anorectal malformation; posterior sagittal anorectoplasty; muscle stimulator; resource-poor